Density‐ and resource‐dependent movement characteristics in a rotifer. (19th February 2013) - Kuefler, Daniel; Avgar, Tal; Fryxell, John M.
Summary: Theory predicts that consumers can increase their energy intake by spending more time within resource‐rich areas and/or by avoiding areas where local competitor densities are high. A consumer whose movements are described by a simple random walk can achieve these objectives by adjusting its turn frequency and/or speed. We recorded movements, as series of steps, by 180 individual rotifers ( Brachionus calyciflorus ) in glass capillary tubes to test the influence of resource density, competitor density and their statistical interaction on movement parameters. Four treatments contrasted opposing levels of algae (resource) and conspecific density in a 2 × 2 factorial design. Our results indicate that density‐ and resource‐dependent behaviours act through different mechanisms to shape patterns of rotifer movement. Turn frequency increased up to twofold in resource‐rich treatments, depending on the presence or absence of competitors. In contrast, swimming speed was 50% greater in the presence of competitors under all treatments, but was only slightly depressed by the presence of resources alone. We show how these two different movement mechanisms may be integrated into predictions of consumer population spread as resource and competitor densities vary. We discuss implications of the contrasting and complementary nature of these different movement mechanisms and their possible adaptations to different environmental stimuli. Abstract : Lay Summary Abstract :